FAKTOR RESIKO KEJADIAN ABORTUS DI RUMAH SAKIT DAERAH KOLONEL ABUNDJANI BANGKO - Rahmi Sari Kasoema; Ainal Mardiah; Yuliandrawati Yuliandrawati (Universitas Fort de Kock Bukittinggi, 2023)
Bleeding can occur at any gestational age. The incidence of bleeding in early pregnancy is often associated with abortion. The frequency of spontaneous abortion in Indonesia is 10%-15% of 5 million pregnancies each year or 500,000-750,000. At the Colonel Abundjani Hospital Bangko, the number of abortions in 2020 was 232 people (25.6%) and in 2021 there were 176 (24.8%) people. The purpose of the study was to determine the risk factors for abortion at the Colonel Abundjani Bangko Regional Hospital in 2022. The study was carried out from February to May 2022 at the Colonel Abundjani Bangko Regional Hospital. Variables are parity, age, disease history, gestational distance, nutritional status, parity and history of abortion. While the dependent variable is abortion, the type of research is Observational, descriptive design. The population of all mothers who have abortions in 2019 - 2021 is 566 people with a sample obtained using purposive sampling of 293 people. The data uses secondary data. Analyzed by univariate analysis. The results showed that more than half of the 167 respondents (57%) were aged 20-35 years. 185 respondents (63.1%) had pregnancy intervals > 2 years. 212 (72.4%) have a parity of 1-3 people. 124 respondents (42.3%) had no history of disease. 224 respondents (76.5%) had normal nutritional status. 122 respondents (41.6%) had missed abortions. The conclusion of this study is that many respondents had missed abortions. It is expected for hospitals to always provide health services in carrying out care for patients, especially health workers on duty in hospitals and provide information in order to improve the quality of health services, especially about problems that occur in pregnant women causing abortion.Keywords: Risk, Abortion Incidence.